Gestão assistencial ao portador de transtorno mental: avaliação de necessidades cuidativas e carga de trabalho - Mukai, Helena Ayako (2012)
Introduction: Knowledge on hospitalized patients nursing care demands and the nursing team s workload permit implementing changes in the care process and in care management. Aims: This study aimed to: 1- Identify the sociodemographic and epidemiological profile of patients with mental disorders; 2- Assess their nursing care needs and, 3- Measure the mean number of care hours delivered and the nursing team s workload. Sample and Method: This descriptive and retrospective research (2006-2010) was conducted at a public neuropsychiatric hospital in the Brazilian Southeast. In this study, 105 mental disorder patients were examined through the application of a patient classification instrument. For statistical treatment, Main Components Analysis, Variance Analysis, Kruskal-Wallis test and Bonferroni s adjustment were used. Results: Hospitalization times of up to 15 years were predominant, with 84 (80%), schizophrenia diagnoses 50 (47.7%) and patients in the discrete care category (73.3%). The nursing/bed index ranged from 0.22 to 0.48, and the nurse/bed index from 0.06 to 0.13; the mean number of care hours from 0.57 to 0.88 (nurses) and from 1.97 to 3.16 (nursing auxiliaries) and the workload from 119.6 to 183 hours. Conclusion: The researchers hope these research results can contribute to the elaboration of mental health policies and equip managers for decision-making and the establishment of action strategies aimed at care planning and quantitative/qualitative staff adjustments.